A Comparative Study on the Numbers of Operations Used in the Computation of Value of Combinations (n¦r) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Several different methods are used to compute the value of combinations. A comparison between the two methods of computing the value of combinations viz traditional method involving the use of factorial notations in the formula of  and the method of computing the value of combinations by the repeated divisions with a specific lower bound ‘p’ associated with ‘n’ where n and p are positive integers is made.